Who should you listen to in a crisis? Differences in communication of central bank policymakers - Jonne Lehtimäki; Marianne Palmu (Journal of Central Banking Theory and Practice, 2022)
Communication has become a vital part of modern monetary policy, and its importance is even higher during a crisis when a central bank has to calm the markets down. This paper studies the information content of different styles of communication from individual central bank policymakers in the European Central Bank and the Federal Reserve during a period of very high economic uncertainty, and whether it differs depending on the role or position of the speaker. The findings suggest that during the financial crisis there was a large variance in the information content of different policymakers and styles of communication.
Keywords: D83; E50; E52; E58; E59; 330; Communication; Monetary Policy; Central banking; Central Banks and Their Policies